2014
DOI: 10.1002/ijc.29245
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of pseudomyxoma peritonei analyzed using next‐generation sequencing and immunohistochemistry

Abstract: Pseudomyxoma peritonei (PMP) is a relatively rare clinical syndrome characterized by neoplastic epithelial cells growing in the peritoneal cavity and secreting mucinous ascites. Our aim was to explore the molecular events behind this fatal but under-investigated disease. We extracted DNA from 19 appendix-derived PMP tumors and nine corresponding normal tissues, and analyzed the mutational hotspot areas of 48 cancer-related genes by amplicon-based next-generation sequencing (NGS). Further, we analyzed the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 44 publications
(118 reference statements)
4
93
1
Order By: Relevance
“…Macrodissection was used when applicable to increase the yield of tumor DNA. Two to fifteen tissue flakes were deparaffinized and genomic DNA was extracted using QIAamp DNA Mini Kit (Qiagen, Venlo, the Netherlands) as previously reported [9]. DNA quality was inspected with NanoDrop spectrophotometer (Thermo Fischer Scientific, Waltham, MA) and agarose gel electrophoresis (with Midori Green Advanced DNA Stain; Nippon Genetics EUROPE GmbH, Dueren, Germany), and DNA concentration was determined using Qubit dsDNA HS Assay Kit and Qubit 2.0 Fluorometer (Molecular Probes/Life Technologies, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Macrodissection was used when applicable to increase the yield of tumor DNA. Two to fifteen tissue flakes were deparaffinized and genomic DNA was extracted using QIAamp DNA Mini Kit (Qiagen, Venlo, the Netherlands) as previously reported [9]. DNA quality was inspected with NanoDrop spectrophotometer (Thermo Fischer Scientific, Waltham, MA) and agarose gel electrophoresis (with Midori Green Advanced DNA Stain; Nippon Genetics EUROPE GmbH, Dueren, Germany), and DNA concentration was determined using Qubit dsDNA HS Assay Kit and Qubit 2.0 Fluorometer (Molecular Probes/Life Technologies, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The pileup files for VarScan somatic were created using SAMTools mpileup (v0.1.19) [16] with default parameters except for -q 1 -Q 10. We estimated tumor cell percentage for each sample both visually from the HE stained slides and from the variant allele frequencies (VAF) of KRAS and GNAS variants obtained from our previous targeted deep sequencing of the same samples [9] (Table 1). The average read coverage of the targeted sequencing was 3,580X, making the VAFs and, thus, tumor cell percentages, more reliable than using VAFs from exome sequencing (average coverage 120X).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Prevalence of KRAS & GNAS mutations in LAMN and PMP tumor samples has been reported in various studies with high variability ranging from 53-100% & 40-63% respectively (Table 1). [21][22][23][24][25][26] Differences in cell enrichment methods, genomic sequencing techniques, regional variation and small number patients in most of these studies may have contributed to this variation. Alakus et al reported KRAS and GNAS mutations in 10/10 and 9/10 tumor samples respectively, which is quite higher than previous studies.…”
Section: Pseudomyxoma Peritonei Genomicsmentioning
confidence: 99%